Periprosthetic joint infections in modular endoprostheses of the lower extremities: a retrospective observational study in 101 patients. Issue 1 (December 2016) - Zajonz, Dirk; Zieme, Almut; Prietzel, Torsten; Moche, Michael; Tiepoldt, Solveig; Roth, Andreas; Josten, Christoph; von Salis-Soglio, Georg; Heyde, Christoph-; Ghanem, Mohamed
Abstract Background Modular mega-endoprosthesis systems are used to bridge very large bone defects and have become a widespread method in orthopaedic surgery for the treatment of tumours and revision arthroplasty. However, the indications for the use of modular mega-endoprostheses must be carefully considered. Implanting modular endoprostheses requires major, complication-prone surgery in which the limited salvage procedures should always be borne in mind. The management of periprosthetic infection is particularly difficult and beset with problems. Given this, the present study was designed to gauge the significance of periprosthetic infections in connection with modular mega-implants in the lower extremities among our own patients. Methods Patients who had been fitted with modular endoprosthesis on a lower extremity at our department between September 1994 and December 2011 were examined retrospectively. A total of 101 patients with 114 modular prostheses were identified. Comprising 30 men (29.7 %) and 71 women (70.3 %), their average age at the time of surgery was 67 years (18–92 years). Results The average follow-up period was 27 months (5 months and 2 weeks to 14 years and 11 months) and the drop-out rate was about 8.8 %. Altogether, there were 19 (17.7 %) endoprosthesis infections: 3 early infections and 16 late or delayed infections. The pathogen spectrum was dominated by coagulase-negative staphylococci (36 %) andStaphylococcus aureus (16 %), including 26 % multi-resistant pathogens. Reinfection occurred in 37 % of cases of infection. Tumours were followed by significantly fewer infections than the other indications. Infections were twice as likely to occur after previous surgery. Conclusion In our findings modular endoprostheses (18 %) are much more susceptible to infection than primary endoprostheses (0.5–2, 5 %). Infection is the most common complication alongside the dislocation of proximal femur endoprostheses. Consistent, radical surgery is essential – although even with an adequate treatment strategy, the recurrence rate is very high. Unfortunately, the functional results are frequently unsatisfactory, with amputation often being the last resort. Therefore, the indication for implantation must be carefully considered and discussed in great detail, especially in the case of multimorbid patients with previous joint infections.